Effect of Acetylcholinesterase Inhibitors on Cerebral Perfusion and Cognition: A Systematic Review - Moyaert, Paulien; Beun, Soetkin; Achten, Eric; Clement, Patricia (Journal of Alzheimer's disease, 2023)
Perfusion imaging has the potential to identify neurodegenerative disorders in a preclinical stage. However, to correctly interpret perfusion-derived parameters, the impact of perfusion modifiers should be evaluated. In this systematic review, the impact of acute and chronic intake of four acetylcholinesterase inhibitors (AChEIs) on cerebral perfusion in adults was investigated: physostigmine, donepezil, galantamine, and rivastigmine. Chronic AChEI treatment results in an increase of cerebral perfusion in treatment-responsive patients with Alzheimer's disease, dementia with Lewy bodies, and Parkinson's disease dementia in the frontal, parietal, temporal, and occipital lobes, as well as the cingulate gyrus. These effects appear to be temporary, dose-related, and consistent across populations and different AChEI types. On the contrary, further perfusion decline was reported in patients not receiving AChEIs or not responding to the treatment. AChEIs appear to be a potential perfusion modifier in neurodegenerative patients. More research focused on quantitative perfusion in both patients with and without a cholinergic deficit is needed to draw conclusions on whether AChEI intake should be considered when analyzing perfusion data.